Design and experimental validation of a single phase grid tied inverter for residential low power applications - Mousmi, Ali; Schellmanns, Ambroise; Elghadhi, Salem; Desouches, Quentin (Institute of Advanced Engineering and Science, 2025)
This paper presents the design and control of a single phase grid tied inverter intended for low power applications in residential sector as part of smart grid environments or solar photovoltaic source integration. The total cost of the converters used in such applications involving low power rates, generally lower than 1 kW, cannot afford expensive components or complex techniques, so, the optimization of the power circuits as well as the simplification of the control algorithms are necessary to meet the specifications. In this purpose, this work presents the design steps of a single phase grid tied inverter including the structure choice, a synchronization algorithm based on the grid voltage zero crossing method, and the algorithm to control the injected power. Different experimental tests have been carried out and show the good performance of the converter which meets the requirements in terms of total harmonic distortion and efficiency.